Giovanni Vecchi, Il concepto di Pedagogía in Hegel. (Dalla educazione estetica a la formazione filosofica dell'uomo), Mursia Editore, Milano, 1975 - Moreno, Jorge H. (1979)
Fil: Moreno, Jorge H. Pontificia Universidad Católica Argentina; Argentina